STUDY ON THE VARIATION OF BED SHEAR STRESS BY USING SWAN MODEL IN CAM RANH BAY AND THUY TRIEU LAGOON - Quang, Nguyen Hao; Ngoc, Pham Khanh; Sasaki, Jun (Vietnam Journal of Marine Science and Technology, 2017)
Turbidity is an important parameter to assess water quality and is an indicator to determine water pollution. In shallow waters, one of the main causes of turbidity is due to resuspension of bed sediment. This process only occurs when water depth is less than one-half the wave length. Meanwhile wave energy will form shear zone and result in resuspension. Bed shear stress is an important quantity to determine the areas where resuspension phenomenon of bed sediment can occur. In this paper, SWAN model was used to calculate and discuss the spatial variation of bed shear stress, taking into consideration the effects of wind velocity and direction at Cam Ranh bay and Thuy Trieu lagoon. The results show that when the wind speed reaches over 5 m/s, high bed shear stress occurs at shallow waters for both the Southwest and Northeast monsoons. When wind speed reaches over 13 m/s, most of the study area is influenced by resuspension.